2013
DOI: 10.1111/jeb.12305
|View full text |Cite
|
Sign up to set email alerts
|

Variation in male effects on female fecundity in Drosophila melanogaster

Abstract: In many species, males have the capacity to directly influence (either positively or negatively) the fitness of their mates and offspring, not only via parental care contributions and/or precopulatory resource provisioning, but also via the post-copulatory activity of those substances passed on to their mates in their ejaculates. Here, we examine how an individual male's identity may be related to phenotypic variation in short-term female fecundity in the model species, Drosophila melanogaster. The effect of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…For females, male identity has been associated with a sizeable percentage of the phenotypic variation in female fecundity [23]. Here, we demonstrated that this variation is owing (in part) to the presence of segregating additive genetic variation, which can account for approximately 10% of female fecundity variation.…”
Section: Discussionmentioning
confidence: 61%
“…For females, male identity has been associated with a sizeable percentage of the phenotypic variation in female fecundity [23]. Here, we demonstrated that this variation is owing (in part) to the presence of segregating additive genetic variation, which can account for approximately 10% of female fecundity variation.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, other female traits that would be expected to be susceptible to sexual conflict dynamics such as egg production showed no IGEs (Edward et al 2014). Another D. melanogaster study recovered a significant effect of male partner identity on female fecundity, consistent with a male IGE affecting female fitness components (Tennant et al 2014). Male IGEs affecting female fecundity appear to be exerted through male mitonuclear epistasis in seed beetles (Callosobruchus maculatus), suggesting a complex interplay between organelle-specific IGEs and sexual conflict (Immonen et al 2016).…”
Section: Empirical Evidence For Iges In Behavioral Ecology Researchmentioning
confidence: 95%
“…An additional source contributing to male fitness was variation in female fecundity. Variation among males in the extent to which they can enhance female egg laying is expected to contribute to overall differences in female fecundity (Smith et al, 2009;Tennant et al, 2014) as well as female condition. However, how much variation in female fecundity contributes to male fitness might also depend on a male's genotype.…”
Section: Discussionmentioning
confidence: 99%